If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + 9)(y + 6) = 0 Reorder the terms: (9 + y)(y + 6) = 0 Reorder the terms: (9 + y)(6 + y) = 0 Multiply (9 + y) * (6 + y) (9(6 + y) + y(6 + y)) = 0 ((6 * 9 + y * 9) + y(6 + y)) = 0 ((54 + 9y) + y(6 + y)) = 0 (54 + 9y + (6 * y + y * y)) = 0 (54 + 9y + (6y + y2)) = 0 Combine like terms: 9y + 6y = 15y (54 + 15y + y2) = 0 Solving 54 + 15y + y2 = 0 Solving for variable 'y'. Factor a trinomial. (9 + y)(6 + y) = 0Subproblem 1
Set the factor '(9 + y)' equal to zero and attempt to solve: Simplifying 9 + y = 0 Solving 9 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + y = 0 + -9 y = 0 + -9 Combine like terms: 0 + -9 = -9 y = -9 Simplifying y = -9Subproblem 2
Set the factor '(6 + y)' equal to zero and attempt to solve: Simplifying 6 + y = 0 Solving 6 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + y = 0 + -6 y = 0 + -6 Combine like terms: 0 + -6 = -6 y = -6 Simplifying y = -6Solution
y = {-9, -6}
| 5x+1=14x-73 | | 6d-2(d-2)=3(d-12) | | (x+7)(2x^2-6x-2)= | | 5b-3=7b+11 | | 4x+10y=35 | | x(5-x)+4(x^1)= | | (5x-6)(4x-7)= | | (5x-7)(3x-2)= | | -7=12-k | | 4d-3=21 | | -32=x-17 | | 237x^2-56x= | | 8x^5y(9x^2+x^2y^3-8y^4)= | | 5a+13=7e-21 | | 3x^2-19x=63 | | 7y-5y=6 | | (4x-5)+(3x-1)= | | (4x^6)(-2x^5)(3x^9)= | | 24.2-18.5P=6.6P-1.9(9P+2) | | 12=k-2+6k | | (-x^2+3x)+(2x^2+7)+(5x-2)= | | 806-?=368 | | z-4=5 | | q+2=3 | | 5x-8x-7= | | 6m+5n-3m+11n= | | 2p^8+5p^4q-12q^2= | | q+.33=.5 | | (5x^2+4x-8)+(3x^2+3x+14)-(8x^2-11)= | | -14y^2-9y^2+12y^2+61xy^2-18xy^2= | | -28-2.6q=-3.8q+4(4.3q+1) | | (3x^2+2x-3)+(5x^2+4x+13)-(8x^2-18)= |